2020
DOI: 10.1080/00049158.2020.1834278
|View full text |Cite
|
Sign up to set email alerts
|

Oil yield and composition of young Santalum yasi in Fiji and Tonga

Abstract: Santalum yasi, a sandalwood native to Fiji and Tonga, is a tree crop of significant economic potential for these countries. Development of a plantation industry underpinned by a breeding program is a high priority for industry development. Gathering information on heartwood development, oil yield and oil composition is a critical step for the domestication and tree breeding of the species. Oil yield and composition were determined for 86 Santalum core samples using gas chromatography and combined gas chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…There is often a temptation or necessity to generate earlier cash income, however, and trees are commonly harvested at around 15 years, at which time only a modest amount of heartwood has usually developed. A survey of trees in Fiji and Tonga in 2018 indicated that harvesting at this age risks losing substantial income, with incomplete heartwood defvelopment evident (Bush, Brophy et al 2020); similar findings were made by Doran et al (2005), who examined young-aged (10-20-year-old) sandalwood including S. album, S. yasi and their hybrid in Fiji and Tonga, and by Jones et al (2006), who studied 14-17-year-old planted S. album at Kununurra, Western Australia. Harbaugh and Baldwin (2007), which examined multiple populations of each species.…”
Section: Cultivationmentioning
confidence: 99%
“…There is often a temptation or necessity to generate earlier cash income, however, and trees are commonly harvested at around 15 years, at which time only a modest amount of heartwood has usually developed. A survey of trees in Fiji and Tonga in 2018 indicated that harvesting at this age risks losing substantial income, with incomplete heartwood defvelopment evident (Bush, Brophy et al 2020); similar findings were made by Doran et al (2005), who examined young-aged (10-20-year-old) sandalwood including S. album, S. yasi and their hybrid in Fiji and Tonga, and by Jones et al (2006), who studied 14-17-year-old planted S. album at Kununurra, Western Australia. Harbaugh and Baldwin (2007), which examined multiple populations of each species.…”
Section: Cultivationmentioning
confidence: 99%
“…Santalum yasi appears to have a higher proportion of βsantalol in its oil than S. album (Doran et al 2005;Bush, Brophy et al 2020). As β-santalol is chiefly responsible for some of sandalwood's signature aromas (Baldovini et al 2011), this trait may be used to positively differentiate the product.…”
Section: Discussionmentioning
confidence: 99%
“…Oil quality is an equally important trait for sandalwood buyers, processors and consumers, with the most highly desired oils meeting the International Organization for Standardization (ISO) standard for East Indian sandalwood oil (ISO 2002-3518) of 41-55% α-santalol and 16-24% β-santalols. Two studies on oil constituents (Doran et al 2005;Bush, Brophy et al 2020) have indicated that pure yasi may be particularly rich in β-santalol, with individual tree samples frequently exceeding the ISO S. album standard. According to one French perfume chemist, the quality of a sandalwood oil for perfume may be enhanced by its minor fragrant constituents as much as by its α-and β-santalol content and also negatively affected by undesirable minor constituents, which may give 'off-characteristics' to fragrance, give rise to allergic responses such as contact dermatitis, or are listed as undesirable in product pharmacopeia.…”
Section: Step 4: Assessing the Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean levels of αand β-santalol in S. macgregorii found by Page, Jeffrey et al (2020) were lower than their respective levels in Santalum yasi Seem. from Fiji and Tonga (Bush, Brophy et al 2020) and S. album in Australia (planted) and Sri Lanka (Brand et al 2012;Subasinghe et al 2017). For Santalum austrocaledonicum Vieill., much variation in the level of santalol was found within and between sites in Vanuatu, but several sites in both Vanuatu and New Caledonia demonstrated higher santalol levels, equivalent to S. album (Braun et al 2005;Page et al 2010;Butaud 2015) and higher than any S. macgregorii population.…”
Section: Introductionmentioning
confidence: 99%